Public Perception of Covid-19 Vaccination Program Policy in Bireuen Regency, Aceh - Aisyah, Ti; Chaidar, Al; Alfiady, T; Aiyub, Aiyub; Maryam, Maryam; Yunus, Saifuddin (Malikussaleh Social and Political Reviews, 2023)
The Covid-19 vaccination policy aims to eradicate the transmission of Covid-19 and reduce mortality or morbidity. However, community participation in the Covid-19 vaccination program in the Pesangan sub-district, Bireun, needs to be improved. Lack of public participation due to public perception of the vaccination program is harmful, low confidence in the quality of vaccines, anxiety and fear of side effects of the vaccine. This study aims to analyse the public perception of the Vaccine-19 Program policy in Pesangan District, Bireuen Regency. The method used in this study is a qualitative research method with a descriptive type. Primary data sources were collected through observations, interviews, and documentation. The results showed that public perception of vaccination risks increased, and many people refused to vaccinate. Only a few people perceive that the vaccine program is essential to ward off the Covid-19 virus so that public health can improve and the community's economy can recover.